The place of museums and the right to the city: a study of space, time and work (Cadernos de Sociomuseologia, 2018)
This study deals with the relationship between the geographic location of museums and visitors. Analyze barriers to visitation of Brazilian museums by the working class and poor, considering the asymmetries between the location of museums and the production and spatial appropriation in major cities comprising this relationship from the geographer concept David Harvey, of uneven geographical development To this end, I will work in an interdisciplinary perspective combining elaborations of Sociology, Geography and Museology. I will use survey data from the Institute of Applied Economic Research (IPEA) on culture, urban mobility, work and free time and also the search Museums in numbers, the Brazilian Institute of Museums (IBRAM).Keywords: museums, cultural equipment, urban mobility, geopolitic, work.